2017
DOI: 10.1002/nau.23149
|View full text |Cite
|
Sign up to set email alerts
|

Are we justified in suggesting change to caffeine, alcohol, and carbonated drink intake in lower urinary tract disease? Report from the ICI‐RS 2015

Abstract: In addition to fluid intake, there is some evidence to support a role of caffeine, alcohol, and carbonated beverages in the pathogenesis of OAB and lower urinary tract dysfunction. Although some findings are contradictory, others clearly show an association between the ingestion of caffeine, carbonated drinks, and alcohol with symptom severity. CONCLUSIONS Given the available evidence lifestyle interventions and fluid modification may have an important role in the primary prevention of lower urinary tract symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 41 publications
1
33
2
5
Order By: Relevance
“…The present scoping review includes 26 studies, far exceeding previous reviews on the role of caffeine in LUTS, which included three to 10 studies each 8,13,25,54 . A synthesis of this present review's results revealed possible beneficial effects of complete caffeine cessation or a reduction to under 100 mg of caffeine per day (equivalent of one cup of percolated coffee) 26 on urgency episodes (level of evidence 2, grade of recommendation B) 24 and nocturnal enuresis episodes (level 4, grade C) 24 .…”
Section: Discussionmentioning
confidence: 97%
“…The present scoping review includes 26 studies, far exceeding previous reviews on the role of caffeine in LUTS, which included three to 10 studies each 8,13,25,54 . A synthesis of this present review's results revealed possible beneficial effects of complete caffeine cessation or a reduction to under 100 mg of caffeine per day (equivalent of one cup of percolated coffee) 26 on urgency episodes (level of evidence 2, grade of recommendation B) 24 and nocturnal enuresis episodes (level 4, grade C) 24 .…”
Section: Discussionmentioning
confidence: 97%
“…It is known that some conditions such as hypertension, diabetes, neurologic diseases, and even cognitive impairment can be related to UI and there is some evidence to support the role of carbonated beverages in the pathogenesis of LUTS . However, there was no evidence to suggest that these factors are more frequently related to nurses than to workers of other professions.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that some conditions such as hypertension, diabetes, neurologic diseases, and even cognitive impairment can be related to UI 40 and there is some evidence to support the role of carbonated beverages in the pathogenesis of LUTS. 41 However, there was no evidence to suggest that these factors are more frequently related to nurses than to workers of other professions. Nurses' behaviors in the workplace, such as poor bladder habits, inadequate liquid consumption, and lifting heavy weights, were associated with LUTS, with one study comparing nurses with secretaries and finding that the nurses presented higher rates, unhealthier habits, and worst QoL.…”
Section: Iciqui-sfmentioning
confidence: 97%
“…Limiting excess fluid intake and changing the type of fluid is advised in most LUTS guidelines. 70 Less is known about the effect of diet and weight loss. 6 Weight loss will decrease hyperfiltration and diuresis.…”
Section: Intake As a Target Of Nocturia Therapymentioning
confidence: 99%